Pelatihan Model Computational Thinking bagi Guru TK dan SD Gaussian Kamil School Semarang - Trisnapradika, Gustina Alfa; Pertiwi, Ayu; Prabowo, Wahyu Eko Aji; Setiyanto, Noor Ageng; Putra Sumarjono, Cornellius Adryan (LPPM UNIVERSITAS DIAN NUSWANTORO, 2024)
CT is the ability to think to solve problems whose solution is computing. CT abilities cannot possibly grow in an instant, CT knowledge and skills need time to grow and develop so that they produce as expected. CT training for kindergarten and elementary school teachers at Gaussian Kamil School will be carried out in several stages, starting with an introduction to the CT concept, practice questions, practicing CT using digital methods, and Unplugged. It is hoped that this training can improve teachers' CT abilities, so that teachers will infuse it with students. Students who receive CT from an early age are expected to be able to be independent and behave better because they are used to solving problems in the correct, fast and efficient way.